Electropermeabilization of apple tissue: Effect of cell size, cell size distribution and cell orientation - Chalermchat Y. (2017)
The influence of the anisotropy of apple tissue and the orientation of applied electric field on electropermeabilization was investigated. Different tissue regions were sampled to perform a series of experiments. The tissue was viewed under the microscope to study cell size, shape and orientation. In a parallel experiment, cylindrical samples of tissue were subjected to pulsed electric fields and the change in electrical conductivity was measured by the voltage-current method. The measured electrical conductivity during pulsing was then converted into a permeability index which defined the relative change in electrical conductivity compared to the electrical conductivity of frozen/thawed tissue that served as a reference of completely damaged tissue. Electrical impedance was also measured to monitor the tissue changes as affected by pulsed electric fields. The results showed that elongated cells taken from the inner region of the apple parenchyma, responded to the electric fields in different ways. Fields of lower intensity were required to permeabilize these cells when the fields were applied parallel to the longest axis of the cells. Other field orientations required greater applied electric fields to permeabilize the cells. No field orientation dependence was observed for round cells that belonged to the outer region of the apple parenchyma. A condition in which a high degree of permeabilization during pulsing and very small change after pulsing were observed could be obtained at an applied field intensity of 900 V cm -1 . Thus reversible electroporation took place. © 2009 IAgrE.